Perception of authenticity of Netong's original La Paz batchoy's consumers and its role in repurchase intention - Baladjay, Aserina Yvonne; Cahiles, Bethooven; Melgar, Mark James; Pama, Ma. Jasmine Carmellie; Panaguiton, Camille (2017.)
Critical success factors in the restaurant industry has been widely studied in published literature and has identified several key factors such as service quality, during experience, food quality, and setting and ambience among others. However, in response to the increase in number of food service outlets, customers are now demanding for authentic food and services from restaurant operators. The researchers observed that authenticity, a factor not thoroughly studied by academicians, is often overlooked as an important factor in restaurant success. However, with the increase in demand from customers, restaurant owners need to be aware and understand how it affects repurchase intention. Authenticity, as a topic is often hard to quantify due to difference on how people judge something as authentic. These views nay be categorized into Objective, Constructive and Existential. Despite the increase in demand for authenticity, published research on authenticity as a factor of repurchase intention is relatively limited. In addition, the different perceptions of authenticity have never been incorporated in the study of authenticity and repurchase intention. Furthermore, there are no published empirical studies on authenticity and repurchase intention with Netong's Original La Paz Batchoy or any restaurnt in Iloilo as the subject matter. This research aims to fill these gaps in literature by determining the effect of differences in perceptions of authenticity to customers' repurchase intention and identify other factors that affects repurchase intention. A survey was conducted to gather the needed data with customers of Netong's as respondents. ANOVA and t-test revealed that a person's perception of authenticity is not related to any socio-demographic characteristic of the particular person. Using Pearson's correlation, it was found out the differences in perceptions does not affect repurchase intention. Authenticity, however, has very strong positive correlation to repurchase intention. To determine other factors that influences repurchase intention, descriptive statistics were used which helped us identify the top three factors. These are Food Quality, Originality and Service Quality.The results of this study contribute to improving how to market a product or service by providing an empirical framework of how authenticity affects consumers' repurchase intention. This study will also assist business owners, specifically those of Netong's to develop their strategies and offer attributes that attract and retain customers.
[Research Paper]. -- Iloilo City : University of the Philippines Visayas - College of Management, May 2017.